Very Artistic! Psycho-Pedagogical Intervention for Social Justice through Socio-Educational Transformation - Odet Moliner García; Auxiliadora Sales Ciges (Universidad Autónoma de Madrid, 2019)
Art, as a possible option for educational intervention, means a personal and professional transformation. This paper shows how inclusive projects related to art allow to develop psycho-pedagogical competences of the future professionals of education, in real contexts; meeting the needs of a community. It is channeled through local institutions that work, from social justice frameworks, with groups that are considered vulnerable. This is a case study about projects that, using a participatory action-research methodology (par), plan and develop proposals that guide the artistic action towards services that address, in a participatory manner, the needs identified in each institution. The collaboration between pedagogues and artists connects psycho-pedagogical action with artistic experience, outlining the transformative possibilities of art. The results allow to identify the transformations in the participants' personal and professional identities. The initial confusion before the relationship between educational psychology and art, forces the students to look at and understand the educational relationship from the equality, creativity and dynamism of socio-cultural relationships, addressing contextual complexity as a determinant for social transformation.